Analysis of the Influence of Audit Quality on Real Profit Management in Companies listed on the Indonesia Stock Exchange - Oktaviana Oktaviana (Universitas Internasional Batam, 2024)
Real earnings management has become a corporate practice in Indonesia and even in other countries in order to optimize maximum operational profit so that it can attract investors' power and advantages that are difficult for auditors to detect so that the reports submitted as factual. The sample test data for this study are companies that are published on the Indonesia Stock Exchange (IDX) with real earnings management as a measurement. This study aims to find out how the influence of the variables Audit Quality, Audit Tenure, Board of Directors, and Board of Directors Independence on Real earnings management. The sample data collected in the framework of the research is in the form of numerical or quantitative data in the amount of 2,015 company data for all business sectors for the period 2016 – 2020 which were published on the IDX. The test results in this study conclude that audit quality and audit tenure have no significant relationship to real earnings management. While the Board of Directors and the Board of Directors of Independence have a significant positive effect on real earnings management.